On the navier‐stokes equation with slip boundary conditions of friction type - Saidi, Fouad (Mathematical Modelling and Analysis, 2007)
In this paper we deal with the boundary value problem for the stationary flow for Newtonian and incompressible fluid governed by the Navier‐Stokes equation with slip boundary conditions of friction type, mostly by means of variational inequalities. Among others, theorems concerning existence and uniqueness of weak solutions are presented. First Published Online: 14 Oct 2010